Pengaruh Periklanan, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Dengan Minat Beli Sebagai Variabel Intervening pada Produk Teh Botol Sosro di Tokma Cibitung (Studi Kajian Pustaka) - E.H.J FoEh, John; Thifal Nur Aini, Rifdah (Dinasti Review, 2023)
The purpose of this study was to measure exogenous variables, endogenous variables, and intervening variables. This research was conducted in Tokma Cibitung. The method used in this study is a survey method using quantitative. The data used in this study are primary data and secondary data. The sampling method in this study used the accidental sampling. The population of this study are all consumers who aee present at Tokma Cibitung who consume Teh Botol Sosro products. The number of samples used in this study were 221 respondents. The data analysis method that will be used in this research is Structural Equation Modeling (SEM) with SmartPLS version 3.0 application and Path Analysis. The results of this study indicate that advertising and product quality have a significant effect on buying interest. Price has no effect on buying interest. Advertising and prices have no effect on purchasing decisions. Product quality and buying interest have a significant effect on purchasing decisions. Advertising and product quality have a significant effect on purchasing decisions through buying interest. Price has no effect on purchasing decisions through buying interest.